Capturing Multidimensional Energy Poverty in South America: A Comparative Study of Argentina, Brazil, Uruguay, and Paraguay - Pereira, Gabriel; González, Arturo; Ríos, Richard (Frontiers in Sustainable Cities, 2021)
Roughly 789 million people have no access to energy and around 2,8 billion people lack access to clean cooking solutions according to the World Bank, and so we also find many people that cannot afford energy (reliable and clean) at the current prices. In the literature, accessibility, availability, and affordability are underlined as key drivers of energy poverty. This research is relevant because it provides a standardized, cross-country, and comparable analysis of multidimensional energy poverty in the region. The study of energy poverty is critical for the development and wellbeing of countries, especially in regions as South America, where this issue can be affected by a geographical, cultural, infrastructure and/or socio-economic differences. In this study we measured the magnitude of energy poverty in Argentina, Brazil, Uruguay, and Paraguay. This methodology considers 3 parameters of energy poverty in the countries: accessibility, availability, and affordability. Through a 2-steps process, first, we calculate the Weighted Average Energy Poverty Index (WAEPI), based in 3 proposed scenarios; and finally, through the Composite Energy Poverty Index (CEPI), we measure the existing gaps, between the countries under study and the benchmark country. Additionally, we decided to focus our analysis on the country that shown the highest level and gaps on multidimensional energy poverty in the region, as a study case to validate the results obtained through the chosen methodology. The results show that during the period of analysis, Paraguay have been the most energy poor country, while Argentina have been the least energy poor country. At the local level, we observed that in Paraguay, despite of being one of the largest producers and exporters of clean hydroelectric energy in the region, still presents high levels of consumption of biomass or coal for cooking, while the electricity only represents 17% of the total final energy consumption in the country. These results could lead the design of energy policies, projects and programs to reduce the multidimensional energy poverty, nationally, as also at the common platform: MERCOSUR. Finally, this study includes an analysis of policy implications and alternatives solutions to eradicate energy poverty in the region.